45. THE ROLE OF ECONOMIC AND GEOGRAPHICAL FACTORS IN THE DEVELOPMENT OF COUNTRIES - Salimov Bakhriddin Lutfullaevich. Tursunpo’latov Jo’rabek Tolibovich (Innovative technologies in construction Scientific Journal, 2023)
The article analyzes that Montesquieu’s socio-philosophical views are quite different from others, that in his philosophy, the first level of attention is focused on economic and geographical factors, that the development of countries is related to the geographical environment, and the existence of three bases of this geographical environment: climate, soil and topography.